(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Transportation Network Vehicle Service (TNVS) is a service drivers provide passengers to take them to their desired destination. Examples of TNVS include Grab and Uber, which are popular in the Philippines. The Human Resource 3 (HR3) system is a strategic tool with five modules: Shift and Scheduling, Time and Attendance, Leave Management, Timesheet Management, and Claim and Reimbursement. The development team used the Agile Scrum methodology to create the HR3 system. They analysed the existing system’s problems and gathered data by researching online. Using the system requirements, the team developed and deployed HR3 features to connect each module and ensure the system’s functionality. To test the new system, the team examined all its submodules and features to ensure they were functional and data was correctly sent. All submodules and features were tested and functional before deploying the HR3 system to ensure proper functionality. The team followed the Agile methodology process to complete the system on time efficiently.